Desativação e regeneração de catalisadores zeolíticos (HY E HZSM-5) utilizados em craqueamento catalítico fluidizado (FCC) - Lima, Andresa Jaciane Cabral de (2015)
The use of catalysts is of fundamental importance to the oil industry, given that they reduce the time and energy required for a reaction to take place, improving efficiency and product quality. In return they end up suffering deactivation, which can be caused by several factors such as: poisoning of active sites for metals, sintering and the formation of coke, which causes obstruction in the pores thus causing the loss of the active phase of the material. After several cycles of use and regeneration, the catalysts are arranged in nature thus becoming a serious environmental problem. Faced with this problem the present study aimed to disable and regenerate acidic zeolites of HZSM-5 and HY types in order to compare the behavior of the same through the techniques: Xray diffraction, adsorption of n-butyl amine Desorption, Analysis Thermogravimetric (TG / DTG) and spectroscopy in the infrared Fourier transform. Disabling was held in an adapted Micro activity reactor. After the reaction the deactivated catalysts were obtained, and then performed regeneration in a muffle furnace. Through the Thermogravimetric curves of n-butylamine desorption was observed a significant increase in the density of acid sites of HZSM-5 average probably new adsorption sites were generated during regeneration. It was also observed that the HZSM-5 zeolite showed about 8% of coke, while HY showed 18% higher this percentage was due to the fact that the zeolite faujasite (FAU) is more acidic, and thus promote further reaction, by the greater coke formation. The coke formed in both zeolites have both aliphatic as aromatic character.